2013
DOI: 10.3109/0886022x.2013.868318
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensinogen gene M235T polymorphism with the risk of IgA nephropathy: a meta-analysis

Abstract: The association between angiotensinogen (AGT) M235T gene polymorphism and IgA nephropathy (IgAN) risk remains elusive. Our aim was to evaluate the association between AGT M235T gene polymorphism and IgAN susceptibility by performing a meta-analysis. Eligible studies were searched according to predefined criteria using electronic databases. Eight studies were identified for the analysis of the association between AGT M235T gene polymorphism and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…age, sex, or diagnostic criteria), or dissimilarities in study design (Bai et al, 2012). Third, diagnosis of IgAN depends on renal biopsy, meaning that those patients who did not agree to this procedure were excluded from the analysis (Mao and Huang, 2014). Finally, any potential influence of the A1166C polymorphism may be effected via gene-gene and gene-environment interactions (Qin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…age, sex, or diagnostic criteria), or dissimilarities in study design (Bai et al, 2012). Third, diagnosis of IgAN depends on renal biopsy, meaning that those patients who did not agree to this procedure were excluded from the analysis (Mao and Huang, 2014). Finally, any potential influence of the A1166C polymorphism may be effected via gene-gene and gene-environment interactions (Qin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al 22 reported that no marked association between AGT M235T gene polymorphism and ESRD was observed in overall populations. Mao et al 23 reported that AGT M235T gene polymorphism was not associated with the risk of IgA nephropathy. Arfa et al 24 reported that AGT M235T gene polymorphism was not associated with the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Renin-angiotensin system-related genes have been postulated as candidate genes for association studies in IgAN but have yielded contradictory results [31,32,33,34,35,36,37]. Among variants in the renin-angiotensin system, insertion/deletion (I/D) polymorphisms in angiotensin-converting enzyme (ACE) genes have been observed.…”
Section: Genetic Studies Of Iganmentioning
confidence: 99%
“…Human leukocyte antigen (HLA) gene family [18,29,30], renin-angiotensin system-related [31,32,33,34,35,36,37], TRAC [38,39] and cytokine-related genes (interleukin-1, transforming growth factor-β1) [40,41] have undergone association studies to test the development and/or progression of IgAN.…”
Section: Genetic Studies Of Iganmentioning
confidence: 99%